Buttering their bread on both sides?: The recognition of sign language s and the aspirations of deaf communities - De Meulder, Maartje; Murray, Joseph J. (Language Problems and Language Planning, 2017)
Abstract In the past two decades, a wave of campaigns to recognise sig n languages have taken place in numerous countries. These campaigns so ught official recognition of national sign languages, with the aim of enhancing signers’ social mobility and protecting the vitality of sign languages. These activities differ from a long history of sign langua ge planning from a ‘language as a problem’ approach largely used by ed ucators and policymakers to date. However, the instrumental rights and social mobility obtained as a result have thus far been limited with educational linguistic and language acquisition rights especially lack ing. This article identifies two reasons for this situation. First, a view of Sign Language Peoples (SLPs) from a medical perspective has le d to confusion about the meaning of linguistic rights for them and led governments to treat sign language planning differently than that for spoken languages. Furthermore, SLPs political participation is hinder ed by recognition being offered by governments without substantial com mitments to financial resources, changes in government practices or gr eater inclusion of sign languages in public life. One exception to thi s trend are sign language planning bodies, but even these face challen ges in the implementation phase. Going forward, we argue that sign lan guage recognition legislation should centre on deaf communities’ conce rns regarding sign language vitality. In addition to a need to ensure acquisition for deaf signers, we contend that while the expansion of h earing (and deaf) new signers can be interpreted in terms of language endangerment it can also be seen as strengthening sign languages’ vita lity.